Interspecific interactions between golden jackals (Canis aureus) and other mesocarnivores at bait stations in Ljubljansko barje - Ana Jaklič; Hubert Potočnik (Natura Sloveniae)
Considering the recent expansion of the golden jackal's (Canis aureus) range, we set out to determine its interspecific interactions at potential food sources with other mesocarnivores in Ljubljansko barje, the area where the first territorial groups in Slovenia were recorded. We set bait and camera traps at six different locations. When analysing the recordings, it seemed that red foxes (Vulpes vulpes) were in all probability avoiding jackals at stationary food sources on a fine spatial scale. In addition, we recorded a case of the possible interference competition between the golden jackal with the European badger (Meles meles).